2014
DOI: 10.1097/qai.0000000000000090
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Boceprevir and Telaprevir on the Pharmacokinetics of Maraviroc

Abstract: Objective:To evaluate the effects of boceprevir (BOC) and telaprevir (TVR) on the pharmacokinetics (PK) of maraviroc (MVC) in healthy volunteers.Methods:In this open-label, fixed-sequence study, 14 volunteers received MVC 150 mg twice daily alone for 5 days (period 1), followed by MVC + BOC 800 mg 3 times daily and MVC + TVR 750 mg 3 times daily, each for 10 days in periods 2 and 3, respectively, with a ≥10-day wash-out. PK was analyzed on day 5 of period 1 and day 10 of periods 2 and 3. Safety was also assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…MVC exposure was shown to increase significantly when coadministered with strong CYP3A/P-gp inhibitors in humans (Hyland et al, 2008). Clinical studies have also indicated that the mean area under the plasma concentration-time curve (AUC) of MVC increased by approximately 9.5-fold when treated with telaprevir (TVR) (Vourvahis et al, 2014). The magnitude of this interaction is much greater than that observed with other strong CYP3A probe inhibitors (e.g., 2.5-fold with ritonavir and 5-fold with ketoconazole) (Abel et al, 2008b;Vourvahis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MVC exposure was shown to increase significantly when coadministered with strong CYP3A/P-gp inhibitors in humans (Hyland et al, 2008). Clinical studies have also indicated that the mean area under the plasma concentration-time curve (AUC) of MVC increased by approximately 9.5-fold when treated with telaprevir (TVR) (Vourvahis et al, 2014). The magnitude of this interaction is much greater than that observed with other strong CYP3A probe inhibitors (e.g., 2.5-fold with ritonavir and 5-fold with ketoconazole) (Abel et al, 2008b;Vourvahis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have also indicated that the mean area under the plasma concentration-time curve (AUC) of MVC increased by approximately 9.5-fold when treated with telaprevir (TVR) (Vourvahis et al, 2014). The magnitude of this interaction is much greater than that observed with other strong CYP3A probe inhibitors (e.g., 2.5-fold with ritonavir and 5-fold with ketoconazole) (Abel et al, 2008b;Vourvahis et al, 2014). Earlier studies have shown an association between MVC plasma trough concentrations and the SLCO1B1 521TC genotype in patients treated with 60 mg MVC plus etravirine or efavirenz (Siccardi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The maraviroc geometric mean AUC and C max for maraviroc and boceprevir treatment relative to maraviroc alone were 3.02 (90 % CI 2.53-3.59) and 3.33 (90 % CI 2.54-3.59). In contrast, maraviroc had no significant impact on the pharmacokinetic profile of boceprevir [18]. The authors concluded that maraviroc should be dosed at 150 mg twice daily when coadministered with boceprevir, similar to the recommendations for maraviroc in combination with other potent CYP3A/P-gp inhibitors [18].…”
Section: Maravirocmentioning
confidence: 75%
“…In contrast, maraviroc had no significant impact on the pharmacokinetic profile of boceprevir [18]. The authors concluded that maraviroc should be dosed at 150 mg twice daily when coadministered with boceprevir, similar to the recommendations for maraviroc in combination with other potent CYP3A/P-gp inhibitors [18]. Use of maraviroc has been associated with hepatotoxicity, and therefore should be administered with caution in patients with pre-existing liver dysfunction, or with HCV or hepatitis B-virus coinfection.…”
Section: Maravirocmentioning
confidence: 82%
See 1 more Smart Citation